Clinico-radiological and bronchoscopic predictors of microbiological yield in sputum negative tuberculosis in Pakistan - Ejaz, Taymmia; Malik, Mahmood Iqbal; Ahmed, Jamal; Azam, Rizwan; Jamal, Yousaf; Saadia, Sheema (Monaldi Archives for Chest Disease, 2021)
To determine association of clinico-radiological factors and radiological activity with diagnostic yield in sputum-smear negative tuberculosis (TB). Prospective observational study in the Military Hospital Rawalpindi (Pakistan) from July to December 2018. Adult patients having no contraindications to bronchoscopy were included. HIV positive patients and those on anti-tuberculosis therapy for more than one week were excluded. High-resolution computed tomography (HRCT) findings were classified based on active and inactive tuberculosis features. Washings were sent for acid-fast bacillus (AFB) smear, GeneXpert assay and cultures. Out of 215 patients, 42.3% (91) were diagnosed with microbiological or histological evidence of TB. On univariate analysis, cavitation (p-value <0.001), soft-tissue nodules (p-value 0.04), and endobronchial mucosal changes (p-value 0.02) were associated with culture positivity. Presence of cavitation (OR= 4.10; CI= 2.18,7.73; p-value<0.001) was the only independent predictor of microbiological yield. Diagnostic yield was 70%, 50%, 12.5% and 8.6% in patients with definitely active, probably active, indeterminate and inactive tuberculosis HRCT features respectively. Sensitivity, specificity, positive predictive value and negative predictive value of HRCT active TB were 95.38% (95% CI 87.10-99.04), 48.00 % (95% CI 39.78-56.30), 44.29% (95% CI 40.31-48.33), 96.00 % (95%CI 88.70-98.66) respectively. There was no significant association between age groups, smoking status and gender with diagnosis of tuberculosis in our study. Radiological activity and certain visualized bronchoscopic changes were associated with good diagnostic performance and can be used as predictive factors in diagnosis of active smear negative tuberculosis.